WAYS TO IMPROVE TEACHING RUSSIAN IN A SECONDARY SCHOOL - Babaeva, S.O (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
Education reform in recent years has yielded positive results. Today, in many different forms of education, renewal and rebirth are felt. Changes, especially in secondary schools, have contributed to the development of education, improving its quality and allowed our teachers to be more creative in their work and demonstrate high professionalism. The first center after the family that forms and educates the person is the school and pedagogical environment. An independent taste, personal beliefs, a sincere civic position, the desire for social growth, the constant search for new things and, in a word, the solution to all personality problems depends on the school and the educational system. Education reform is one of the directions of state and educational policy. Work with the public should also be an integral part of the school and teacher. The introduction of subject curricula in our republic is of interest to parents. Collaboration with the school and the teacher will help them realize their dreams. This article discusses the results of a survey among high school students about the quality of teaching the Russian language.